AKTIVITAS ANTIJAMUR EKSTRAK ETANOL PALA (Myristica fragrans HOUTT.) TERHADAP Malassezia furfur DAN Tricophyton mentagrophytes - Muhamamad Fakhrur Rajih; Nur Asma Somadayo (Jurnal Ilmiah Farmasi Farmasyifa, 2023)
Indonesia is a tropical country that has fair temperature and humidity supporting the growth of pathogenic fungi. Pathogenic fungi commonly encountered infecting humans in Indonesia are the species Malassezia furfur and Trichophyton mentagrophytes. Nutmeg (Myristica fragrans Houtt.) is one of the Indonesian plants known to have potential antifungal activity. The purpose of this study was to examine the antifungal activity of the nutmeg ethanol extract against Malassezia furfur and Trichophyton mentagrophytes, determining the Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MKC) as well as testing the comparative value of nutmeg ethanol extract with ketoconazole. The research method used in testing the antifungal activity and the comparative value of the ethanol extract of nutmeg was the diffusion method for the paper disc technique and the microdilution method for testing the determination of MIC and MKC values. The results of this study show that the nutmeg ethanol extract had antifungal activity against Malassezia furfur and Trichophyton mentagrophytes.The MIC and MKC values of the nutmeg ethanol extract were the same for Malassezia furfur and Trichophyton mentagrophytes, namely the MIC value of the ethanol extract was 2,5%. Meanwhile, MKC value for ethanol extract was 5%, .The comparative values of ketoconazole antifungal activity with ethanol extract of the nutmeg against Malassezia furfur were 1:34, whereas against Trichophyton mentagrophytes were 1:12